INVENTORY SYSTEM AT PT. MOTORCITY USING VISUAL BASIC 6.0 PROGRAMMING LANGUAGE - Defrizal Defrizal; IRE Puspa Wardhani, SKom, MMSi (Jurnal Sistem Informasi, 2007)
Post-crisis (1997) until today, Indonesia is in the intensive supervision of the WorldBank and IMF. However, following the IMF's policy seems not so profitable forIndonesia. At the end of 1997, began a change that in one term is called, times hadchanged. Currently humans live in a new era with new symptoms. That is, the powerof capital and all its derivatives (derivatives) on the order of living together (sharedlife).In this era of helter-skelter, a new political-economic order, born of the liberaleconomic revolution, emerged. His heart is the privilege of obtaining capital from avariety of territorial and national order of the rules. These symptoms gave birth to anew monster on a global scale, namely the strength of international business.Amid the business competition, especially in Indonesia, apparently share of motorvehicle sales are still very promising, as evidenced in Jakarta alone would sell 100units of motorcycles per day. Therefore, in line with the increasing number ofvehicles using it more and more also request the motor as the spare parts ofmotorcycle maintenance. Sale of motor spare parts business is quite profitableincluding one of which is the sale of motor spare parts is very well known in the areaof Tangerang Cileduk which business is developing very rapidly.